ANALISIS PENGHITUNGAN BIAYA SATUAN (UNIT COST) TINDAKAN POLI GIGI KLINIK PRATAMA X MENGGUNAKAN METODE TIME DRIVEN ACTIVITY BASED COSTING - Erfandi Ahmad; Diah Ayu Puspandari; Anastasia Susty Ambarriani (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2021)
Background: The high demand for dental and oral care in the community has led to an increase in Dental Poly visits to the PratamaX clinic. Determining the unit cost of polydental procedures is an important factor in clinic financing and increasing clinic revenue.Until now, the clinic owner has never evaluated the cost of dental poly surgery correctly and has not referred to the cost analysis ofthe service unit.Objective: To analyse the unit cost per Dental Poly procedure at Pratama X Clinic by using the Time Driven Activity Based Costing(TDABC) method.Methods: Descriptive observational study, using primary and secondary data from the clinic with the aim of obtaining a unit costcalculation of dental poly procedures. The design of this research was cross sectional and the type of data used was quantitative data.The results of the calculation and cost analysis to determine the unit costs of dental poly procedures in the form of tartar cleaning, dentalfillings with composite resin materials, tooth extraction and dental braces treatment (fixed orthodontics) by tracing costs related to thecost center of the procedure and other parts. that supports action. Results: Based on the unit cost calculation per procedure at thedental clinic, the Time Driven Activity Based Costing cost system imposed indirect costs in calculating unit costs at the Pratama XClinic. Because the Pratama X Clinic did not accurately classify direct and indirect costs, Pratama X Clinic was not accurate in allocating the costs, number and working hours of ineffective PratamaX Clinic employees.Conclusion: According to the data obtained, the application of Time Driven Activity Based Costing resulted in higher levels of dental care compared to the Pratama X Clinic, except for dental fillingswith small composite resin and dental orthodontics.